THE IMPLICATIONS OF THE LEGISLATIVE CORRUPT PRACTICES ON THE DEMOCRATIC CONSOLIDATION IN THE NIGERIA’S FOURTH REPUBLIC - Yusuf, Yusuf Abdu; Haji Yusoff, Kamarul Zaman; Zengeni, Knocks Tapiwa (Journal of Techno-Social, 2018)
This study analyses the corrupt practices in the Nigerian democracy with specific reference to national legislatures. Using thematic analysis after conducting semi structured interviews, the paper argues that, legislative corrupt practices have become one of the greatest threats to the Nigeria democratic consolidation; it reveals that, corrupt practices are responsible for the poor implementation of public policies in health, education and other infrastructures, it also contributes to the youth unemployment, poverty and national crisis. The paper opines that, corrupt practices of legislative members are inimical and obstacle to democratic consolidation in Nigeria, since the legislature is an institution that is expected to consolidate democracy. Until the institution has been strengthened in its oversight function, scrupulous screening of the legislature is undertaken before the election, the strengthening of recall back mechanism, and the comprehensive approach to deter corrupt practices by the anti-graft institutions, consolidated democracy would not be attained in Nigeria.